Produtividade e popularidade de autores na literatura de educação: análise bibliométrica e comparativa (2011-2015) - Coimbra, Lourdes Cristina Araujo (2018)
This research presents a comparative analysis in three periodicals of Education, namely: Brazilian Journal of Education (Brazil), Lusófona Magazine of Education (Portugal), Science Education International (United Kingdom), all classified as Qualis A1, period 2011 to 2015. As for the methodological procedure, a Bibliometric technique was used to analyze citations, an area of Information Science (CI), based on the work of Marshakova (1981), a qualitative-quantitative and bibliographical research, a descriptive research method, and a transversal cut. The objective was to investigate and analyze the productivity and popularity of authors in the area of Education in the light of CI. Through this research it was also possible to identify characteristics and particularities of the studied area when comparing the set of descriptors / keywords used by the authors in their articles to show the problems faced by this community in their countries. We analyzed 14,346 citations found in 460 journal articles. For productivity, 891 authors were investigated, of which, 201 published individually and 690 in coauthoring, a current practice in science. The relative popularity was calculated on 6,486 authors, who obtained a total of 225 most cited authors in works of other researchers. The data revealed that the authors' preferred channel in Brazil and Portugal are the books and in the UK the scientific journal.